Temporal dynamics of cortisol-associated changes in mRNA expression of glucocorticoid responsive genes FKBP5, GILZ, SDPR, PER1, PER2 and PER3 in healthy humans - Yurtsever, Türkan; Streit, Fabian; Foo, Jerome Clifford (Psychoneuroendocrinology, 2019)
Secretion of the stress hormone cortisol follows a circadian rhythm and is stimulated following stress exposure. Cortisol regulates the transcription of several genes, primarily through activation of the glucocorticoid receptor (GR). Previously, we showed an upregulation of PERIOD genes PER1 and PER3 after pharmacological/glucocorticoid challenge in vivo and in vitro. The current study aims to investigate the temporal association between unstimulated, diurnal cortisol secretion and the expression of selected GR-target genes (PER1, PER2, PER3, FKBP5, GILZ and SDPR) in vivo to determine the timing of the most pronounced coupling between cortisol and mRNA expression. Unstimulated plasma and saliva cortisol concentrations and gene expression levels in whole blood were measured every 15 min from early morning until 16:00 h in 18 healthy men. Time-lagged correlations of cortisol concentrations with mRNA expression levels were assessed allowing lags between -240 and + 240 min. Strong positive correlations at non-zero lags between cortisol levels and the expression of FKBP5 (plasma: r = 0.74 (CI = 0.65-0.81), p <  0.001, lag + 90 min; saliva: r = 0.71 (CI = 0.61-0.78), p <  0.001, lag + 75 min), and GILZ (plasma: r = 0.59 (CI = 0.46-0.69), p <  0.001, lag + 30 min; saliva r = 0.53 (CI = 0.41-0.63), p <  0.001, lag +15 min) were observed. Expressions of PERIOD genes and SDPR correlated only weakly with cortisol (all |r| < 0.25). Our findings demonstrate strong correlations between cortisol secretion and gene expression in humans under unstimulated conditions. The observed time-lags can guide future research aiming to characterize glucocorticoid-dependent gene expression in clinical samples with stress-related disorders.
Available online 30 November 2018
Gesehen am 30.01.2020